EVENTR - DESIGN OF AN EVENT MANAGEMENT MOBILE APPLICATION USING ONTOLOGY - B, RAJESH KANNA; V, VISWANATHAN; AJ, GEORGE EBBINASON (Asian Journal of Pharmaceutical and Clinical Research, 2017)
An event is a special occasion that occurs when few or more people gather together to fulfill their personal, cultural or organizational objectives. WithÂ many events happening every day, few handy tools are available to help an event organizer to initiate, track and propagate an event. Often importantÂ data such as contacts, mails are saved by the organizer in some apps like Excel, calendar, mobile contacts, and mailbox, but not easily retrieved whenÂ needed for a follow-up event. Some of the information belongs to common events are not been grouped categorically, so it could not be suitable toÂ relate the similar actions with respect to events which are associated to each other. Follow-up events usually use almost similar data from the previousÂ season, but every time the organizer ends up spending more time searching for the previous records and sometimes fail to retrieve. Event based appsÂ are available in the mobile environment very few in number, and especially such follow-up concentrated event tracker application is not available.Â Hence, Eventr is designed to fulfill this purpose. Eventr will solve this issue by initiating event, automating simple tasks, record critical data till theÂ event day, this information are stored in the form of Eventr ontology. Since it is ontology based event representation, it would make possible to identifyÂ the intermediate tasks of a particular event and to retrieve the tasks associated with the event to the event organizer for the next season. Â Â